Do Errors on Classic Decision Biases Happen Fast or Slow? Numeracy and Decision Time Predict Probability Matching, Sample Size Neglect, and Ratio Bias - Ryan Corser; Raymond P. Voss; John D. Jasper (Journal of Numerical Cognition)
Higher numeracy is associated with better comprehension and use of numeric information as well as reduced susceptibility to some decision biases. We extended this line of work by showing that increased numeracy predicted probability maximizing (versus matching) as well as a better appreciation of large sample sizes. At the same time, we replicated the findings that the more numerate were less susceptible to the ratio bias and base rate neglect phenomena. Decision time predicted accuracy for the ratio bias, probability matching, and sample size scenarios, but not the base rate scenarios. Interestingly, this relationship between decision time and accuracy was positive for the ratio bias problems, but negative for the probability matching and sample size scenarios. Implications for research on cognitive ability and decision biases are discussed.